Measuring pro-environmental behavior: Review and recommendations. (June 2019) - Lange, Florian; Dewitte, Siegfried
Abstract: Any scientific attempt to understand, predict, or promote pro-environmental behavior requires an adequate measurement tool for the assessment of pro-environmental behavior. The multidisciplinary interest in pro-environmental behavior has generated a large variety of such tools, ranging from domain-general and domain-specific self-report measures, field observations conducted with the help of informants, trained observers, or technical devices, to behavioral tasks for use in the laboratory. The present review discusses this broad spectrum of existing approaches to the measurement of pro-environmental behavior, their strengths and weaknesses, as well as possibilities to improve upon them. From this review, we deduce several recommendations for the development, selection, and application of measures in pro-environmental behavior research. We conclude by stressing the importance of established and validated measures for a cumulative science of pro-environmental behavior. Highlights: Reviews approaches to the measurement of pro-environmental behavior. Covers self-reports, field observations, and laboratory assessment. Discusses strengths and weaknesses of measurement approaches. Recommends measurement approaches and tools dependent on research objectives. Highlights the need for psychometrically established measures.